Gendered Perceptions for Identifying Ecosystem Services in the Arid Ecosystem of Wadi Araba in Jordan - AL-ASSAF, Amani; ALBALAWNEH, Abeer; HJAZIN, Amgad; KABARITI, Rabab; ABU NOWAR, Lana; ALWIDYAN, Jafar; ALBASHBSHEH, Ghadeer; DIAB, Mai; ABU HAMMOUR, Wafa’a; ALJAAFREH, Safaa; AL-SHISHANY, Salsabeel; HADDAD, Nizar (Journal of Environmental Management and Tourism, 2022)
This study aimed to explore how ecosystem services (ES) identification varies among the local communities based on gender perceptions, considering the differences in usage and access to natural resources. We conducted research through two methods; focus groups and personal interviews. Four focus groups were formed in four communities in Wadi Araba (WA), Southern Jordan. A structured face-to-face interview method was used to evaluate a random sample of 200 residents. A binary logistic analysis was conducted to explore how the respondent's gender is seen to influence the type and use of services, and their perceptions of services in an arid ecosystem. The analysis generated three models; the first model showed that women were able to recognize and use provisioning services related to livestock production as they use rangeland for grazing for long periods and long daily hours, and the second model results reflected those women were able to recognize few ES. The identified services were linked to income-generating activities for a long time. The third model indicated that men were more likely to recognize and indicate the establishment of government services in support of the region as a result of the thriving and developed tourism sector.